Adopsi Belanja Online selama Pandemi Covid-19: Pengujian Model Unified Theory of Acceptance and Use of the Technology pada Generasi Z - Felix Thaddeus Christianto; Rully Arlan Tjahyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The COVID-19 pandemic has created a new reality in terms of shopping, including consumption patterns among Generation Z. The pandemic has shifted offline shopping to online platforms by leveraging technology. This research aims to examine the influence of the Unified Theory of Acceptance and Use of Technology (UTAUT) model on behavioral intention. This study also investigates the impact of COVID-19 fear on behavioral intention. The respondents in this study are from Generation Z, and the sample size consists of 259 participants. Data collection for this research is conducted using a questionnaire. Validity, reliability, and classical assumptions tests are performed prior to hypothesis testing. Hypothesis testing is done using multiple linear regression analysis. The results of this study indicate that the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, as well as COVID-19 fear, collectively and partially, significantly influence behavioral intention. The recommendations for future researchers are to include a broader range of variables that may influence behavioral intentions beyond the variables examined in this study and to test the use behavior. Subsequent studies are expected to expand the geographical scope to encompass regions that may possess diverse cultures and characteristics in responding to technological advancements.